REALISASI PRINSIP KESANTUNAN DALAM TUTURAN WALIKOTA SURABAYA TRI RISMAHARINI PADA TALKSHOW TELEVISI - Amiera Thoriq (Sekolah Tinggi Bahasa Asing Yapari-ABA, 2021)
The objective of this research is to describe the realization of politeness principles within the speech of Tri Rismaharini, mayor of Surabaya which appeared in talkshows on television. The main theory of the research is Geoffrey Leech’s Politeness Principles (1983).This qualitative research used data transcript noted from the talkshows that had her as a guest. The drawn conclusion is that all maxims in the politeness principles occurred in the conversations. Those are The Tact Maxim, The Generosity Maxim, The Approbation Maxim, The Modesty Maxim, The Agreement Maxim and The Maxim of Sympathy.